Numerical investigation of heat transfer & hydrodynamic performance of nanofluids in forced convection - Choo, Jian Feng (Nanyang Technological University, 2020)
In 1995, Choi predicted that the cooling rate from traditional fluid heat transportation medium would not be enough for the exponentially increasing heat output produced by microelectronics. Choi found that nanofluid might be one of the solutions to this problem. In the recent years, there has been many theoretical and experimental papers tackling different parts of nanofluids, from derivation of theoretical expression and experimental setup of nanofluid properties, to numerical studies. However, most would approximate nanofluid to single-phase model due to its low volume concentration. This approximation might have overlooked key details on the relationship between solid volume fraction and heat transfer coefficient and pressure drop. Therefore, this research paper will discuss the small details that might explain these phenomena. To answer these uncertainties, this paper will use both Single Phase and Eulerian Granular multiphase model for the numerical investigation of Aluminum-Oxide/water nanofluid of solid volume fraction from 0% to 10% that flows in steady state laminar internal flow, through a half sinusoidal wavy microchannel with constant heat flux along the straight surface. Both the Eulerian Granular multiphase and single-phase model will be investigated to further describe the relationship between solid volume fraction with pressure drop and heat transfer coefficient. The results predicted an increment of solid particle will increase the overall heat transfer coefficient as well as pressure drop while comparing with base fluid. Nanofluid still behave predominantly like liquid because both phases have similar temperature and velocity profile and plot. Nanofluid pressure drop and heat transfer coefficient is proportional to volume fraction at any Reynolds number. The thermal boundary thickness varies with solid volume fraction, while velocity boundary layer thickness is independent of solid volume fraction. Granular kinetic energy and granular pressure do not affect much of heat transfer coefficient and pressure drop as particle diameter might be too small. Validation of numerical studies must be done by running nanofluids in the already built experimental setup. Moreover, the need to standardized procedures such as using similar nanofluid properties for experimental and theoretical studies is needed to build a stronger foundation in the field of nanofluids. Particle physics might also be an avenue to investigate for further analysis to describe relationship of heat transfer coefficient, pressure drop and solid volume fraction.